Penerapan Evaluasi Holistik dalam Kegiatan Pembelajaran : Literature Review (Current Research in Education: Conference Series Journal, 2023)
Education plays an important role in preparing quality human resources. Quality education is education that is able to compete with various challenges that occur now and in the future. Therefore, evaluation needs to be done as a benchmark for achieving a learning goal. However, in practice the evaluation process has not been implemented comprehensively and systematically so that the results have not been able to be viewed objectively. This study aims to determine the process of implementing a holistic assessment. This study uses a systematic literature review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with topic areas of interest to phenomena, with certain relevant research questions. The results show that the implementation of holistic assessment has been carried out based on the 2013 curriculum, using holistic assessment makes it easier for teachers to assess students' abilities. Holistic assessment is used as the best assessment to use because this assessment assesses students in real terms.